Human rights activism and the end of the cold war a transnational history of the Helsinki network - Snyder, Sarah B., 1977- (Human rights in history., 2011)
"This book explores how a network of human rights activists emerged in the aftermath of the 1975 Helsinki Final Act and over time fundamentally reshaped East-West diplomacy"--